2017
DOI: 10.1186/s13014-017-0878-9
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term patient reported outcomes following radiation therapy for oropharyngeal cancer: cross-sectional assessment of a prospective symptom survey in patients ≥65 years old

Abstract: BackgroundGiven the potential for older patients to experience exaggerated toxicity and symptoms, this study was performed to characterize patient reported outcomes in older patients following definitive radiation therapy (RT) for oropharyngeal cancer (OPC).MethodsCancer-free head and neck cancer survivors (>6 months since treatment completion) were eligible for participation in a questionnaire-based study. Participants completed the MD Anderson Symptom Inventory-Head and Neck module (MDASI-HN). Those patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 26 publications
3
28
0
1
Order By: Relevance
“…With a median follow‐up of nearly 7 years, the current study highlights that >15% of patients may experience long‐term QOL‐altering dysfunction in swallowing after treatment. Although it was not analyzed longitudinally in our study, patients have previously demonstrated marked worsening in swallowing function at 6 months to 1 year after definitive IMRT for OPC, with partial recovery by 2 years . By limiting our cohort to those who completed treatment 1 year or more before the survey, we largely excluded those who had acute or subacute symptoms of dysphagia that may recover.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With a median follow‐up of nearly 7 years, the current study highlights that >15% of patients may experience long‐term QOL‐altering dysfunction in swallowing after treatment. Although it was not analyzed longitudinally in our study, patients have previously demonstrated marked worsening in swallowing function at 6 months to 1 year after definitive IMRT for OPC, with partial recovery by 2 years . By limiting our cohort to those who completed treatment 1 year or more before the survey, we largely excluded those who had acute or subacute symptoms of dysphagia that may recover.…”
Section: Discussionmentioning
confidence: 99%
“…Although these have been explored for other symptoms on the MDA S I‐HN (dry mouth scores ≥6 for xerostomia 15 ), to the best of our knowledge, a clinically meaningful MDA S I‐HN‐S cutoff score has not yet been validated. Because no consensus cutoff score for the MDA S I‐HN‐S has been identified, a value ≥6 to represent moderate/severe symptoms was chosen based on published data of optimal cutoff points from composite items and other single items on the MDA S I‐HN . In RPA, an MDA S I‐HN‐S cutoff score of ≥6 was validated to best distinguish QOL‐altering dysphagia symptoms, as measured by the EQ‐VAS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies (63.6%) assessed patients with heterogeneous HN topographies [Murphy et al, 2010;Xiao et al, 2013;Rosenthal et al, 2014;Kirca and Kutlutürkan, 2017;Barnhart et al, 2018;Chiang et al, 2018;Ridner et al, 2018], 2 studies (18.2%) assessed patients with oropharyngeal/laryngeal tumors [Haisfield-Wolfe et al, 2012;Eraj et al, 2017], and 2 studies (18.2%) assessed patients with nasopharyngeal tumors [Xiao et al, 2017;McDowell et al, 2018]. Eight studies (72.2%) reported specific information on patients' stage of disease, from which 6 (54.5%) assessed patients in clinical stage I-IV [Haisfield-Wolfe et al, 2012;Rosenthal et al, 2014;Eraj et al, 2017;Kirca and Kutlutürkan, 2017;Xiao et al, 2017;McDowell et al, 2018] and 2 (18.2%) assessed patients with advanced disease (clinical stage III/IV) [Xiao et al, 2013;Chiang et al, 2018].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%